Linguistic Identities in the Arab Gulf States Waves of Change (Taylor & Francis, 2022)
"Combining empirical and theoretical approaches from a range of disciplines, Linguistic Identities in the Arab Gulf States examines current issues surrounding language and identity in the Arab Gulf states. Organized in four parts, the book addresses the overarching theme of 'waves of change' in relation to language and power, linguistic identities in the media, identities in transition, and language in education. The authors of each chapter are renowned experts in their field and contribute to furthering our understanding of the dynamic, changeable, and socially constructed nature of identities and how identities are often intricately woven into and impacted by local and global developments. Although the book geographically covers Gulf region contexts, many of the concepts and dilemmas discussed are relevant to other highly diverse nations globally. For example, debates surrounding tolerance, diversity, neoliberal ideologies in English-medium instruction (EMI), media representation of language varieties, and sociolinguistic inequalities during coronavirus communication are pertinent to regions outside the Gulf, too. This volume will particularly appeal to students and scholars interested in issues around language and identity, gender, language policy and planning, multilingualism, translingual practice, language in education, and language ideologies."
English
Keywords: Language teaching & learning (other than ELT); Sociolinguistics; Analysis, anthropology, Arab, culture, change, discourse, exclusions, gender, identity, ideology, inclusion, literature, media, linguistic, language, monolingual, narratives, semiotic, translanguaging